Studi Literatur: Analisis Pekerjaan Dalam Konteks Manajemen - Astuti, Devi; Jamilus (Jurnal Manajemen DIVERSIFIKASI, 2024)
Job analysis is a crucial process in human resource management aimed at gaining aprofound understanding of the tasks, responsibilities, and qualifications associated with aspecific position within an organization. Within the management context, job analysis plays akey role in crafting clear job descriptions, determining necessary job specifications, andproviding a foundation for effective employee management. This article presents a holisticview of job analysis, exploring the steps involved, its objectives and benefits, as well asvarious types and methods that can be utilized in the process. By understanding thesignificance of job analysis in a management context, organizations can enhance efficiency,productivity, and employee satisfaction, thus fostering a more dynamic and sustainable workenvironment